A double mixing process to greatly enhance thermal conductivity of graphene filled polyamide 6 composites. (November 2019) - Ren, Yanjuan; Zhang, Yafei; Guo, Haichang; Lv, Ruicong; Bai, Shu-Lin
Abstract: Tremendous investigations have been recently conducted to increase the thermal conductivity (TC) of nanofiller filled thermoplastic composites. However, the agglomeration of nanofillers limits their loading and is a bottleneck to further increase the TC of composites. In this work, a preparation technique combining the benefits of both solution mixing and melt blending is proposed, with which high loading and good dispersion of graphene sheets (GSs) filled polyamide 6 (PA6) matrix composites are achieved. Noteworthily, the through-plane TC of the composites reaches 3.55 W m −1 K −1 with 20 wt% GSs, corresponding to a TC enhancement of 1167% compared to pure PA6. The excellent performance can be attributed to high loading and uniform dispersion of GSs, which facilitate the formation of thermally conductive network for efficient heat transfer. An effective medium theory model by taking the filler-to-matrix and filler-to-filler interfacial effects into consideration is also proposed to perceive the behind mechanism. The theoretical calculation agrees well with our experimental results. Moreover, we find the Young's modulus of the composite increases significantly and the tensile strength nearly remains unchanged even at a GSs filler loading of 20 wt%. The results provide an effective and facile route for developing low-cost and highly conductive thermoplastic composites.